2021
DOI: 10.1371/journal.pone.0250642
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicle-encapsulated miR-181b-5p, miR-222-3p and let-7a-5p: Next generation plasma biopsy-based diagnostic biomarkers for inflammatory breast cancer

Abstract: Inflammatory breast cancer (IBC) is a rare, but aggressive entity of breast carcinoma with rapid dermal lymphatic invasion in young females. It is either poorly or misdiagnosed as mastitis because of the absence of a distinct lump. Small extracellular vesicles (sEVs) circulating in liquid biopsies are a novel class of minimally invasive diagnostic alternative to invasive tissue biopsies. They modulate cancer progression via shuttling their encapsulated cargo including microRNAs (miRNAs) into recipient cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…For instance, deregulation of miR-200b, miR-200c, miR-205, and miR-487 has been observed in lung cancer [ 12 ], supporting the concept that smoking-related epigenetic changes might be considered as putative biomarkers for lung diseases. Moreover, the development of novel cost-effective extracellular vesicle-based liquid biopsy techniques aid miRNA-based diagnostics, as recently demonstrated for inflammatory breast cancer [ 28 ].…”
mentioning
confidence: 99%
“…For instance, deregulation of miR-200b, miR-200c, miR-205, and miR-487 has been observed in lung cancer [ 12 ], supporting the concept that smoking-related epigenetic changes might be considered as putative biomarkers for lung diseases. Moreover, the development of novel cost-effective extracellular vesicle-based liquid biopsy techniques aid miRNA-based diagnostics, as recently demonstrated for inflammatory breast cancer [ 28 ].…”
mentioning
confidence: 99%
“…Previous reports have indicated that EVs containing anti-tumor drugs can induce cell apoptosis in HCCs (Slomka et al, 2020). Furthermore, EVs containing miRNA mimics such as let-7a have been found to induce cell apoptosis in breast cancer (Ahmed et al, 2021). In addition, EVs have the ability to regulate autophagy.…”
Section: The Function Of Evs In Apoptosis and Autophagymentioning
confidence: 95%
“…MiR-150-3p has been suggested as a prognostic biomarker for HCC [ 97 ]. MicroRNAs are important diagnostic biomarkers for breast cancer [ 212 , 213 ]. It is important to identify not only miRNAs but also lncRNAs for diagnosis [ 214 ].…”
Section: Potential Of Evs For Liquid Biopsymentioning
confidence: 99%